Colorado Clash - Sharpe, Jon (New York Signet, 2009)
After Skye Fargo comes across a dead man near the town of Cawthorne, he aims to take the body to town for burial. But he soon learns someone in Cawthorne has developed a taste for murder--and the Trailsman might be the killer's next course.
Keywords: Fargo, Skye (Fictitious character)